Regional Economic Development and Private Car Ownership in Java, Indonesia - Andriana Kumalasari; Djoni Hartono (Universitas Airlangga, 2026)
Objective: This study examines the relationship between regional economic development and private car ownership across 114 cities and regencies on Java Island, Indonesia, between 2015 and 2023, using data from Statistics Indonesia (BPS) and the Ministry of Transportation. Methods: The study applies a Correlated Random Effects (CRE) panel model with instrumental variable techniques to identify both within- and between-associations and to address potential endogeneity. The analysis is conducted using the full sample and subsamples by region and by city/regency size to capture heterogeneous effects across Java. Findings: The results indicate that per capita regional GDP and mean years of schooling are positively and significantly associated with private car ownership across all cities/regencies. In the Jakarta Metropolitan Area (JMA), population density is negatively and significantly associated with private car ownership, reflecting the region’s disadvantages of private car use. Conversely, in large cities/regencies, road infrastructure has a negative and significant association with car ownership, but population density maintains a positive and significant association, indicating insufficient public transportation services. Originality/Value: This study contributes to the literature by providing the first Java-wide panel analysis that jointly estimates within- and between-effects and addresses endogeneity in the economic development–car ownership nexus. Practical/Policy Implication: In the JMA region, first- and last-mile connectivity should be strengthened. In large cities/regencies, integrated multimodal transport systems should be developed to suppress the growth of private car ownership. In small cities/regencies, the Central Government should play a key role in supporting investment and planning for sustainable transportation.